A randomized dose-finding study demonstrating the efficacy and tolerability of albiglutide in Japanese patients with type 2 diabetes mellitus. (June 2014) - Seino, Yutaka; Inagaki, Nobuya; Miyahara, Hajime; Okuda, Inaha; Bush, Mark; Ye, June; Holland, M. Claire; Johnson, Susan; Lewis, Eric; Nakajima, Hiromu
Abstract Objective: To investigate the optimal dosage/regimen and to evaluate the efficacy and safety of albiglutide in Japanese patients with type 2 diabetes mellitus. Research design and methods: This was a randomized, double-blind, placebo-controlled, multicenter, parallel-group, dose-ranging, superiority study in Japanese patients with type 2 diabetes mellitus. Patients (n = 215) who were treatment naive or washed out of one oral antidiabetic drug were randomized to placebo or albiglutide 15 mg weekly, 30 mg weekly, or 30 mg every other week (biweekly). Clinical trial registration: NCT01098461. Main outcome measures: The primary end point was the change from baseline in HbA1c at week 16, measured using the Japan Diabetes Society standardization scheme and presented here using the National Glycohemoglobin Standardization Program equivalents. Other measures of efficacy as well as safety and population pharmacokinetics and pharmacokinetics/pharmacodynamics of albiglutide were assessed. Results: Baseline HbA1c was 8.53%. There was a statistically significant difference between each albiglutide treatment group and placebo for change from baseline in HbA1c at week 16, with treatment effects of −0.89% for 15 mg weekly, −1.55% for 30 mg weekly, and −1.10% for 30 mg biweekly (P < 0.0001 for all groups vs placebo). By week 16, 63.0% and 33.3% of patients in the 30 mg weekly albiglutide group compared with 6.0% and 0% of patients in the placebo group achieved HbA1c <7.4% and <6.9%, respectively. No serious adverse events were related to study therapy; no deaths occurred. Nasopharyngitis was the most frequently reported adverse event in all treatment groups (n = 43 [20.3%]). Conclusions: Albiglutide exhibited therapeutic hypoglycemic effects with good tolerability among Japanese patients with type 2 diabetes mellitus; the 30 mg weekly dose was the most efficacious in this study. The 16 week duration of the study prevents generalizing these conclusions to longer treatment periods.